Social Media as an Arena for Digital Jihad: An Analysis of Online Da'wah on Tiktok, Youtube, and Instagram - Ramadhan, Muhammad Alief Raihan; Alfajri Firdaus, Rizki; Surawan, Surawan (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2025)
YouTube, TikTok, and Instagram have become key platforms for digital da’wah, particularly in reaching younger audiences. This study applies a descriptive qualitative approach with content analysis of ten purposively selected popular videos. The analysis focused on themes, rhetoric, visualaudio elements, and audience responses. The findings reveal unique characteristics of each platform. YouTube is marked by long, systematic, and argumentative sermons that enable deeper understanding. TikTok emphasizes short, concise, emotional, and viral content, making it effective for audiences with limited attention spans. Instagram highlights visual aesthetics and reflective messages, supported by interactive features such as comments and Q&A. These patterns illustrate the need for adaptive communication strategies aligned with algorithms and media consumption habits. The notion of “digital jihad” is interpreted as a non-physical struggle to spread Islamic values online while prioritizing ethics, substance, and engagement. Digital da’wah thus serves not only as religious communication but also as cultural activism that strengthens Islamic identity among youth in the digital era.